Towards a sustainable information society : deconstructing WSIS - Servaes, Jan, 1952-; Carpentier, Nico (European Consortium for Communications Research (Series), 2006)
The Information Society is one of the recurrent imaginaries to describe present-day structures, discourses and practices. Within its meaning is enshrined the promise of a better world, sometimes naively assuming a technological deus ex machina, in other cases hoping for the creation of policy tools that will overcome a diversity of societal divides. With the two-phased World Summit on the Information Society (WSIS), the United Nations attempted to stimulate the development of such tools. Simultaneously, the WSIS is a large-scale experiment in multistakeholderism. The objective was to create a.